2021
DOI: 10.3390/nu13124276
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Cardiometabolic Benefits of Plant Products Containing Mixed Phenolics and Polyphenols in Postmenopausal Women: Insufficient Evidence for Recommendations to This Specific Population

Abstract: Menopause is characterized by endocrine and physiological changes and is often accompanied by increased body weight and cholesterol, glucose intolerance, and/or hypertension. These alterations are associated with increased risk for cardiovascular diseases (CVDs) and Type II diabetes mellitus (T2DM) that may be moderate by dietary plant phenolic compounds. In this review, we examine the current evidence of the impact of a variety of plant products (foods, extracts, beverages) rich in a mixture of phenolics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 95 publications
(151 reference statements)
0
13
0
Order By: Relevance
“…Despite the increasing number of intervention trials performed in this research area, proving these properties in humans remains challenging. In multiple meta-analyses and reviews looking at the beneficial effects of dietary bioactive constituents in humans, the overall recurrent messages remain the same, i.e., ‘the heterogeneity in the trial design including differences in the sample population, analytical procedures and data assessment leads to inconsistent results and increases the difficulty in interpreting those effects’, ‘interindividual variability in the responses to diet precludes the full understanding and establishment of its efficacy and true health benefits’ [ 106 , 107 , 112 , 113 , 183 , 184 , 185 ]. In the present review, we have explored the situation in a series of human intervention studies in which changes in the levels of TNF-α were investigated in response to different dietary approaches.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the increasing number of intervention trials performed in this research area, proving these properties in humans remains challenging. In multiple meta-analyses and reviews looking at the beneficial effects of dietary bioactive constituents in humans, the overall recurrent messages remain the same, i.e., ‘the heterogeneity in the trial design including differences in the sample population, analytical procedures and data assessment leads to inconsistent results and increases the difficulty in interpreting those effects’, ‘interindividual variability in the responses to diet precludes the full understanding and establishment of its efficacy and true health benefits’ [ 106 , 107 , 112 , 113 , 183 , 184 , 185 ]. In the present review, we have explored the situation in a series of human intervention studies in which changes in the levels of TNF-α were investigated in response to different dietary approaches.…”
Section: Discussionmentioning
confidence: 99%
“…A first critical issue is ‘sample size’. It has been repeatedly indicated that ‘given the variability of the results and the generally small size effects observed in dietary interventions with bioactive constituents, larger clinical trials are needed’ [ 106 , 107 , 112 , 113 , 183 , 184 , 185 ]. Indeed, it is widely acknowledged that larger group sizes will improve the validity of the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Undoubtedly, the question is interesting, opening new intriguing fields studying the effects of the combination "Mediterranean diet" and soy isoflavones intake, with the ambitious target to better define in post-menopausal women [25] the relationship between…”
mentioning
confidence: 99%